2023
DOI: 10.1080/17482631.2023.2216034
|View full text |Cite
|
Sign up to set email alerts
|

“It’s not time for us to sit down yet”: how group exercise programs can motivate physical activity and overcome barriers in inactive older adults

Abstract: Purpose Physical activity and exercise are critical for older adults’ physical and mental health. The purpose of this qualitative study was to richly capture the motivators of and barriers to engaging in physical activity in previously inactive older adults who participated in a three-arm randomized controlled trial (RCT) of eight-week group exercise interventions. Methods We conducted a qualitative content analysis of individual interviews with fifteen participants—fiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 74 publications
0
4
0
Order By: Relevance
“… Cheng (2017) suggested that the most common challenges experienced by carers of people living with dementia relate to Behavioral and Psychological Symptoms associated with Dementia, as they can substantially contribute to distress for the carer. A study by Royse et al (2023) identified that positive social influences and the desire to spend time with family members can mitigate the challenges of older people in engaging in exercise. The factors in motivating older people to exercise can inform future programs in designing the online-delivered exercise program for people with dementia.…”
Section: Discussionmentioning
confidence: 99%
“… Cheng (2017) suggested that the most common challenges experienced by carers of people living with dementia relate to Behavioral and Psychological Symptoms associated with Dementia, as they can substantially contribute to distress for the carer. A study by Royse et al (2023) identified that positive social influences and the desire to spend time with family members can mitigate the challenges of older people in engaging in exercise. The factors in motivating older people to exercise can inform future programs in designing the online-delivered exercise program for people with dementia.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, self-efficacy plays a crucial role in this process. Royse's research also suggests that exercise can enhance self-efficacy and increase PA, creating a positive cycle that promotes a positive lifestyle [ 52 ]. In Wu's research, encouraging the elderly to participate in choreography in intergenerational dance activities not only improves the self-efficacy and sense of accomplishment of the elderly but also improves their creativity and activity motivation [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…Besides beliefs and individual preferences, group-based settings may embed several interpersonal factors predictive to exercise engagement and maintenance. Indeed, qualitative studies reported that self-reliance, social bonds, peer support and exercise learning influence self-efficacy, which is highly determinant for long-term PA maintenance in older adults [76,77,269,270]. Additionally, group-based settings may support involvement and empowerment to promote self-efficacy [163], while home-based settings seem to induce only short-term improvements that were lost after follow-up [271].…”
Section: Unsupervised Home-based or Supervised Group-based?mentioning
confidence: 99%